PENGARUH ENERGI METABOLIS DAN PROTEIN RANSUM TERHADAP PERSENTASE KARKAS DAN ORGAN DALAM AYAM KAMPUNG (Gallus domesticus) BETINA UMUR 30 MINGGU - Wiranata, G. A.; Kristina Dewi, I G. A. Mayani; Indrawati, R. R. (Jurnal Peternakan Tropika, 2014)
Research on the effect of ration with Metabolic Energy and Crude Protein levels on the ration to the percentage of 30 weeks’ female chicken carcasses and internal organs which held in Peguyangan Kaja village, North Denpasar, Bali Province. The design used in this study is completely randomized design (CRD) with four treatments with the content of the ration Metabolic Energy (ME) 3100 kcal / kg and Crude Protein (CP) 22 % (treatment A) and treatment B, C and D by using Energy Metabolic and Crude Protein and for each treatment received 3000 kcal / kg and 20 % ; 2900 kcal / kg and 18 % ; 2800 kcal / kg and 16 %. Each treatment received four replications with the result that there are 16 units of the experiment. There are 48 chickens were used in the research. Variables observed in this study were heavily cut, carcas weight, carcass percentage, liver percentage, heart percentage, lymph percentage, and kidneys percentage. Then, the data were analyzed with analysis of variance, if there is a difference between the real treatments (P<0.05) then followed by the Duncan's Multiple Range Test according to Steel and Torrie (1989). The results showed that administration of rations with a proportion of Crude Protein and Metabolic Energy (3100 kcal / kg and 22 % (140,90); 3000 kcal / kg and 20 % (150) ; 2900 kcal / kg and 18 % (161,11) ; 2800 kcal / kg and 16 % (175)) did not really different (P>0.05) to heavily cut, carcass percentage, internal organs percentage such as the liver, heart, lymph and kidney in 30 weeks’ female chicken. The conclusion the effect of energy ration and protein ration is the influence of metabolizable energy and protein ration of 3100 kcal / kg and 22% (140.90) gives slaughter weight, carcass weight, carcass percentage and the percentage the better lower kidney of the treatment ration metabolizable energy and protein with 3000 kcal / kg and 20%; 2900 kcal / kg and 18%; 2800 kcal / kg and 16%.
Keywords: kampung female chicken, energy, protein, body weight, carcas and inner organs